Azilsartan attenuates cardiac damage caused by high salt intake through the downregulation of the cardiac (pro)renin receptor and its downstream signals in spontaneously hypertensive rats. Issue 11 (November 2018) - Komaki, Hisaaki; Iwasa, Masamitsu; Hayakawa, Yuka; Okamoto, Chihiro; Minatoguchi, Shingo; Yamada, Yoshihisa; Kanamori, Hiromitsu; Kawasaki, Masanori; Nishigaki, Kazuhiko; Minatoguchi, Shinya
Abstract We examined whether the stimulation of the angiotensin II AT1 receptor increases the expression of the cardiac (pro)renin receptor ((P)RR) and its downstream signals and whether the blockade of the angiotensin II AT1 receptor by azilsartan decreases the expression of the cardiac (P)RR and its signaling in spontaneously hypertensive rats (SHRs) with a high-salt intake. Rats received normal-salt (0.9%) chow, high-salt (8.9%) chow, normal-salt chow with 1 mg/day of azilsartan, and high-salt chow with 1 mg/day of azilsartan from 6 to 12 weeks of age. Rats with normal-salt chow were administered 100 ng/kg/min of angiotensin II by osmotic minipump from 6 to 12 weeks of age. A high-salt diet and angiotensin II significantly increased the systolic blood pressure; overexpressed cardiac (P)RR, phosphorylated (p)-ERK1/2, p-p38MAPK, p-HSP27, and TGF-ß1; enhanced cardiac interstitial and perivascular fibrosis, cardiomyocyte size, interventricular septum (IVS) thickness, and left ventricular (LV) end-diastolic dimension; and decreased LV fractional shortening. Azilsartan decreased systolic blood pressure, cardiac expressions of (P)RR, p-ERK1/2, p-p38MAPK, p-HSP27, and TGF-ß1, cardiac interstitial and perivascular fibrosis, cardiomyocyte size, and LV diastolic dimension, and improved LV fractional shortening. In conclusion, azilsartan attenuates cardiac damage caused by high salt intake through the downregulation of the cardiac (pro)renin receptor and its downstream signals in SHRs.